Dehydrated pork manure by-product: effect of a chitosan amendment on bacterial community and common scab incidence - Roy, Julie; Lafontaine, Pierre; Chabot, Rock; Beaulieu, Carole (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2009)
Chitosan amendment modified the composition of a microbial community associated with dehydrated pork manure by-product. The amended product (biosolid PC) contained a lower number of anaerobic bacteria than the non-amended product (biosolid P). Chitosan also significantly reduced the fungal population. A 16S rRNA gene bank constructed from DNA extracted from the bacterial community associated with both P and PC biosolids revealed that bacterial orders Xanthomonodales, Pseudomonadales, Enterobacteriales, Burkholderiales, Actinomycetales, Bacillales, Clostridiales and Lactobacillales were found in both biosolids. Bacteria from the Stenotrophomonas genus were abundant in both biosolids. However, the addition of chitosan appeared to induce changes in the population of some bacterial genera. For example, clones carrying a 16S rRNA gene corresponding to the Bacillus genus were doubled in biosolid PC. In field trials carried out to test their effect on common scab incidence, biosolids P and PC were applied as potato seed treatment. Biosolid P increased disease incidence by a factor of 1.33 and 2.85 in two independent experiments. However, when chitosan was added to the seed treatment, the stimulating effect of biosolid P on common scab was cancelled out.